Physical, motor and anthropometric testing variables that distinguish soccer teams of different participation levels - Gird, C. C.; Coetzee, B. (Journal of Human Movement Studies, 2006)
The aim of this study was to identify the physical, motor performance and anthropometric testing variables that distinguish soccer teams of different participation levels. Fifteen Uniwest (classed äs elite), twelve Vaal Triangle Techniken (classed äs sub-elite) and sixteen North-West Sports Academy players (classed äs the developmental team) were selected for this study. Each player was subjected to a test battery that consisted of 8 physical and motor tests äs well äs 14 anthropometric measurements. The cluster analysis reduced the amount of test variables (48) to only 20. The multivariate analysis of variance revealed that playing position had no significant effect on the different testing variables. The results of the proceeding discriminant analysis showed that the following testing variables were the most important discriminators of soccer players of different participation levels: isokinetic right leg dorsiflexion peak torque (F=13.26), agility (F=2.62), right leg hamstring flexibility (F=0.49), isokinetic right leg plantarflexion peak torque (F=2.88), muscle mass percentage (F=9.70), speed over 5m (F=2.77) and abdominal muscle strength (F=0.68). The classification functions that were developed from these seven variables had an average success rate of 94.74% in classifying the soccer players into their separate groups. Isokinetic right leg dorsi and plantarflexion peak torque, agility, right leg hamstring flexibility, muscle mass percentage, speed over 5m and abdominal muscle strength are the physical, motor performance and anthropometric testing variables that have an average of 94.74% success rate in distinguishing soccer players of different participation levels.